Potential Tax Revenue On Luxury Pets (Studies In Indonesia) - Nugraha, Satria Yudha; Sa’diyyah, Dewi Khalimatus; Prasetyaningrum, Oktavia Rizki; Al Hazmi, Raldin Alif (Journal of Law, Administration, and Social Science, 2024)
The phenomenon of flexing, which is excessive showing off behavior where a person tries to solidify a position in the social environment to meet the need for appreciation and validation from others regarding their social status. In Indonesia, this phenomenon takes many forms, one of which is flexing related to pets. Some people have animals that are classified as luxury pets. Luxury pets, often referred to as exotic pets or luxury pets, refer to animals that are not commonly used as pets and are usually relatively expensive. Given the characteristics of luxury goods mentioned in the VAT and STLG Law applicable in Indonesia, it is stated that luxury goods are not basic needs, consumed by certain people, consumed by high-income people and to show status. Therefore, Pets classified as Luxury Pet should be subject to STLG considering the development of pet lovers increases over time, for example, cats, dogs and fish. This research is expected to provide the imposition of new types of taxes for the DGT so as to increase state revenue, especially in the tax sector